Efficacy and safety of phosphatidylinositol 3-kinase inhibitors in patients with chronic lymphocytic leukemia: a meta-analysis and systematic review. Issue 9 (2nd September 2022) - Wen, Yanting; Meng, Li; Zhang, Xian; Gao, Qian
ABSTRACT: Background: Phosphatidylinositol 3-kinase (PI3K) inhibitors demonstrate promising effects in the treatment of relapsed/refractory chronic lymphocytic leukemia (CLL). Emerging evidence of the therapeutic effects of the PI3K inhibitors in various aspects remains controversial. Research design and methods: This meta-analysis was used to evaluate the efficacy and safety of PI3K inhibitors based on a synthesis of the data generated by randomized controlled trials (RCTs) of patients with CLL, by searching PubMed, EMBASE, Cochrane Central Register of Controlled Trials, and ClinicalTrials.gov registry. Results: Five RCTs with 1593 patients were included. The PI3K inhibitors significantly improved progression-free survival (PFS), the chance of overall response, and partial response compared to the control arm. Regarding adverse events (AEs), the PI3K inhibitors increased the risk of pyrexia, chills, diarrhea, decreased appetite, vomiting, rash, pneumonia, and upper respiratory tract infection. Conclusions and expert opinion: Available evidence showed significant improvements over conventional therapy in PFS of the PI3K inhibitors in patients with CLL, with relatively manageable AEs.